Navigating Halal-Critical Materials In The Fashion Industry: A Socio Legal Study Of Non Halal Animal Derived Products - Anisa Fadilah Zustika; Auliya Ghazna Nizami; Kamilatus Salsabia; Sania Ardiana (Journal of Sharia Economic Law, 2026)
The rapid growth of the global fashion industry has increased demand for leather-based products such as shoes, bags, wallets, jackets, and accessories. However, pig skin is still used in some fashion products, and its material composition is often not clearly disclosed to Muslim consumers. This raises concerns regarding sharia compliance, transparency, and consumer protection. This study examines the use of pig skin in fashion products from the perspective of Islamic law and explores Muslim consumer awareness of this issue. A qualitative socio-legal approach was employed to integrate normative Islamic legal principles with empirical practices in the fashion industry. Data were collected through document analysis of Islamic legal sources and halal regulations, in-depth interviews with Islamic scholars, halal facilitators, fashion MSME actors, and Muslim consumers, as well as field observations. Thematic analysis was applied to identify patterns of compliance and responses to halal market demands. The findings indicate that pig skin is inconsistent with halal principles because it is prohibited in Islam. Although Muslim consumer awareness has increased, many consumers still experience difficulties identifying product materials due to inadequate labeling. From a business perspective, the use of non-halal materials may reduce consumer trust and harm brand reputation, whereas transparent material disclosure and halal certification enhance customer confidence and market competitiveness. The study emphasizes the need to strengthen halal literacy, improve labeling transparency, and reinforce halal supply chain governance in Indonesia's fashion industry